P111 Bronchoalveolar Lavage does not affect the Acute Inflammatory Response Following Bronchoscopy and Mediastinoscopy. (19th November 2012) - Jones, RO; Murchison, JT; Casali, G; Simon, EJ; Anderson, N; Simpson, AJ; Walker, WS
Abstract : Objective: Bronchoalveolar lavage (BAL) may be used to investigate acute inflammation following thoracic surgery. However, BAL has previously been found to induce an acute phase response in healthy and critically-ill patients complicating research analysis (1, 2). We sought to examine the impact of BAL in thoracic surgery patients hypothesising that BAL would not lead to a significant additional acute inflammatory response. Methods: Seventeen patients undergoing lung cancer staging bronchoscopy and mediastinoscopy were randomly assigned to have 220mls 0.9% NaCl BAL before surgery (n=10) or no BAL (n=7). Blood samples were taken pre-operatively followed by 6 and 24 hours post-operatively. Exhaled nitric oxide (eNO) was also measured at a flow rate of 50mls/sec at these times. All patients had a CXR at 24hrs and were evaluated for evidence of SIRS using pre-defined criteria. Results: IL-6 and CRP increased post-operatively peaking at 6hrs and 24hrs respectively however there was no statistically significant difference between the increase for BAL and non-BAL patients (p>0.05). There was no significant increase or variation between the groups for IL-2, IL-4, IL-10, TNF-α or IFN-γ (p>0.05). eNO tended to decrease in the BAL group and increase in the non-BAL group at 6hrs although there was no significant difference between the groups (p=0.167). Post-operative CXR atelectasis developed in 3 patients (2 BAL). One patient in each group developed SIRS. Conclusion: BAL has minimal impact on acute inflammation following bronchoscopy and mediastinoscopy. It may therefore be used to safely and reliably obtain samples for research or microbiology purposes in thoracic surgery patients. Huang Y-C T, Bassett MA, Levin D, Montilla, Ghio AJ. Acute Phase Reaction in Healthy Volunteers After Bronchoscopy with Lavage. Chest 2006; 129 (6): 1565–9. Terashima T, Amakawa K, Matsumaru A et al. BAL Induces an Increase in Peripheral Blood Neutrophils and Cytokine Levels in Healthy Volunteers and Patients with Pneumonia. Chest 2001; 119 (6): 1724–1729.